Strategi Marketing Public Relations PT Ciputra Golf Surabaya Dalam Upaya Meningkatkan Loyalitas Pelanggan - Zahra Lea Almaira Scarletta; Rini Ganefwati; Delmarich Bilga Ayu Permatasa (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study discusses the marketing strategy of public relations in increasing customer loyalty. Customers are the heart of the company so that customer loyalty is needed by the company, one of which is by implementing the right marketing strategy and adjusted to the company's target market. The purpose of this study is to systematically determine how the Marketing Strategy of Public Relations in Increasing Customer Loyalty of PT. Ciputra Golf. The method used in this study uses a qualitative method with a descriptive method analysis approach, the researcher conducted interviews with key informants, namely Public Relations of PT Ciputra Golf and Supporting informants such as Company Management, Field Guides and customers. From the results of the study, it can be concluded that the marketing strategy carried out by Public Relations of PT Ciputra Golf uses three strategies consisting of Pull, namely an attractive strategy through social media, customers will understand what promos and events are at Ciputra Golf. Push, namely a strategy that encourages through social media and also two-way communication between employees and customers, so customer loyalty will be successfully achieved by PT. Ciputra Golf. Pass strategy, namely a strategy that influences by using social media content and taglines that attract customers to come back to enjoy the services provided by PT Ciputra Golf.